2003
DOI: 10.1007/s00394-003-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatty acids on expression of endothelial leukocyte adhesion molecules

Abstract: IL-1alpha increased ICAM-1,VCAM-1, and E-selectin expression compared to controls. Incubation with IL-1alpha together with linoleic acid reduced the expression of ICAM-1 and VCAM-1 in contrast to palmitic acid. Furthermore, in the presence of linoleic acid a tendency of diminished adhesion of monocytes is seen. The results indicate that a reduced expression of cell adhesion molecules may be relevant to the antiatherogenic effects of linoleic acid. This is in contrast to the properties of palmitic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…In contrast, several studies have reported anti-infl ammatory effects of LA. In one such study, LA in combination with IL-1α was found to decrease the expression of adhesion molecules ICAM-1, VCAM-1, and E-selectin from endothelial cells when compared with IL-1α treatment alone, with decreased monocyte adherence as a fi nal end point [38]. In support of the anti-infl ammatory effects reported for LA, other investigators have found that endothelial cell activation decreases as the level of unsaturation increases [39,40].…”
Section: Effects Of Fatty Acids On Vascular Infl Ammationmentioning
confidence: 86%
“…In contrast, several studies have reported anti-infl ammatory effects of LA. In one such study, LA in combination with IL-1α was found to decrease the expression of adhesion molecules ICAM-1, VCAM-1, and E-selectin from endothelial cells when compared with IL-1α treatment alone, with decreased monocyte adherence as a fi nal end point [38]. In support of the anti-infl ammatory effects reported for LA, other investigators have found that endothelial cell activation decreases as the level of unsaturation increases [39,40].…”
Section: Effects Of Fatty Acids On Vascular Infl Ammationmentioning
confidence: 86%
“…By contrast, linoleate (C18:2 6), a polyunsaturated FFA with controversial effects on endothelial activation (25,26), did not promote IL-6 expression in CAECs and had only a minor, possibly endotoxin-mediated, IL-6Ϫinducing effect in CASMCs. As to the FFA specificity of this cellular response, palmitate was by far the most potent IL-6Ϫinduc-ing FFA in CAECs.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying these associations are, however, far from clear. Whereas monoand polyunsaturated FFAs, such as oleate (C18:1 9), linoleate (C18:2 6), arachidonate (C20:4 6), eicosapentaenoate (C20:5 3), and docosahexaenoate (C22:6 3), have been convincingly demonstrated to modulate endothelial functions (23)(24)(25)(26)(27)(28), very little is known about the role of saturated FFAs in vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pro-atherogenic effects of SFA have been demonstrated [13,14] whereas the properties of the n-6 PUFA precursor are still discussed [15][16][17][18]. Indeed, some authors demonstrated a positive correlation between LA intake and a proinflammatory response and/or an increased risk to coronary diseases [19] whereas others showed that n-6 PUFA family intake protect against atherosclerosis through anti-inflammatory properties [8,15,[20][21][22].…”
Section: Introductionmentioning
confidence: 93%
“…Dietary fatty acids are known to modulate endothelial functions [7,8]. On one hand, some studies pointed out neutral and/or anti-atherogenic properties of monounsaturated fatty acids (MUFA) and n-3 PUFA families, respectively [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%